DaVinci Resolve Guru: Moving Timelines Between Editing Apps. - Inhofer, Patrick (linkedin.com, 2016)
Understand the process of sharing timeline data between editing apps like Premiere Pro, Final Cut Pro X, and Avid Media Composer, and DaVinci Resolve.